Islamic Religious Activities (Rohis) as a Medium in Forming Students' Social Skills at SMK Negeri 2 Palangka Raya - Novita Sari; Ajahari, Ajahari; Surawan, Surawan (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This research aims to examine the role of Islamic Religious Activities (Rohis) at SMK Negeri 2 Palangka Raya in developing students' social skills, with reference to social learning theory and character education. This study uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing processes, with source and technique triangulation to ensure the validity of results. Findings show that Rohis activities such as Quranic reading and writing, tilawah (Quranic recitation), habsyi (religious chanting), and community service not only strengthen spiritual and moral aspects, but also contribute significantly to the development of students' social skills, such as the ability to collaborate, empathize, take responsibility, resolve conflicts, and express opinions assertively. These activities also have a positive impact on students' ability to build healthy interpersonal relationships and increase their self-confidence in the school environment. In conclusion, Rohis activities function not only as a religious medium, but also as a strategic tool in shaping students' character and social skills that align with 21st-century learning needs and the demands of today's multicultural society.